THE DEVELOPMENT OF AMAZING NGANJUK ETHNOMATHEMATICS-BASED APPLICATION FOR THE PLANE SHAPE MATERIAL FOR GRADE IV OF ISLAMIC ELEMENTARY SCHOOL - Tanti, Yusi Krisma; Annisa, Choirul; Ratno, Puspoko Ponco (UIN Sunan Kalijaga Yogyakarta, 2023)
This research-and-development is motivated by the need for the use of culture-based learning media in the mathematics subject because, during learning, teachers often only focus on material without any integration with culture, and there is a lack of students’ knowledge of the culture that exists in Nganjuk Regency. The purpose of this research and development is to examine the ethnomathematics in the culture of Nganjuk and analyze the development and feasibility level of the ethnomathematics-based Amazing Nganjuk application for the plane shape material of grade IV in Islamic elementary schools. This study is of Research and Development (R&D) type that uses the Alessi and Trollip model of 3 stages, which include planning, design, and development. The product trial was carried out through the alpha test and beta test. The alpha test was conducted by media experts and material experts while the beta test was conducted by the fourth-grade students of Islamic Elementary School (IES) Khadijah Sukorejo Loceret Nganjuk. The result of this research and development was an ethnomathematics-based android application. The ethnomathematics elements found in this study were Jayastamba monument, wayang timplong, gamelan gender, and demung. The results of the media and material validation showed an average percentage of feasibility level of 96% and 93.75% with a very feasible category for use in the beta test. The beta test obtained an average percentage of 97% with the category indicating that the fourth-grade students strongly agreed with the use of the Amazing Nganjuk application to learn plane shapes. The application that the researchers have developed is deemed suitable for use as a learning medium, especially for the plane shape material.